Effectiveness Of Using Pegadaian Sharia Digital Application Services (PSD) At PT. Pegadaian Syariah Branch Radin Intan Lampung - Anisa, Heldinia; Supriyaningsih, Okta; Kurniati, Erlin; Cahyani, Anisa Binar (Universitas Islam Negeri Raden Intan, 2024)
The presence of technology in this increasingly advanced era has a very high impact, technology is here to facilitate the daily activities of the social community. One of these technological advances is manifested in the development of a service system for customers in the form of digital applications, one of which is PT. Pegadaian which launched the Pegadaian Syariah Digital (PSD) application, this application was launched in 2018 to make it easier for customers to make transactions. The aims of this study were (1) to find out the operationalization of the Pegadaian Sharia Digital application at the Sharia Pawnshop branch of Radin Intan Lampung (2) to find out the effectiveness of the Pegadaian Sharia Digital application service at the Pegadaian Sharia of Radin Intan Lampung. This study uses a descriptive qualitative research method with a type of field research. Respondents in this study were 4 customers who used the PSD application and 4 FROM Pegadaian Sharia of Radin Intan Lampung. The data sources for this research are primary data obtained directly from observations and interviews with customers and the Sharia Pawnshop branch of Radin Intan Lampung and secondary data obtained from books, literature in the form of journals that support research and other references. In analyzing research data, the authors use the E-Servqual Theory proposed by Zeithaml about the quality of online services.